Watermelon stomach o Vascular Ectasias of the Gastric Antrum (Gastro Antro / Vascular Ectasias - Perrier, José Pedro; Piazze, Alvaro; Maglione, Oscar (Cirugía del Uruguay, 2003)
Report of three cases of Gastro Antral Vascular Ectasis (watermelon type stomach) in patients with differente primary diseases which determi-ned repeated blood replacements and led to other therapeutic measures. All three patients underwent electro-coagulation of ectasias. Results were initially good, though subsequendly two of them had to undergo gastric antrum resection. The report includes a revision of this pathology